Role of climate and other factors in determining the dynamics of tick and tick-transmitted pathogen populations and distribution in western, central and eastern Africa - Githaka, Naftaly W.; Kanduma, Esther G.; Bishop, Richard P. (CAB International, 2021)
This expert opinion discusses the potential impact of climatic change on vector abundance, survival and transmission of tick-borne pathogens in western, central and eastern Africa. It also discusses the following cases: (1) Rhipicephalus microplus with a focus in West and Central Africa and (2) northern expansion of Rhipicephalus appendiculatus into South Sudan through anthropogenic cattle movement.